M&E Universe - intrac (2019)
The M&E Universe is a free, online resource developed by INTRAC to sup port development practitioners involved in monitoring and evaluation ( M&E). It consists of a series of short papers (2-6 pages) on different subjects related to M&E. It can be explored through an online platfor m (intrac.org/universe) that is compatible with most web browsers. The M&E Universe is designed for M&E practitioners with different levels of experience and expertise in M&E, from those new to M&E who want an entry level into the subject to experienced practitioners wanting to b roaden their knowledge. Initial contact with the Map will provide peop le with a starting point for understanding different aspects of M&E an d how they link to each other. More experienced practitioners can brow se the Map to identify more advanced subjects of interest, such as sam pling methods, different forms of evaluation, organisational M&E syste ms and complex methodologies for data collection and analysis.